Chinese herbal compound Huangqin Qingrechubi capsule reduces lipid metabolism disorder and inflammatory response in gouty arthritis via the LncRNA H19/APN/PI3K/AKT cascade - Xianheng Zhang; Jian Liu; Yanqiu Sun; Qin Zhou; Xiang Ding; Xiaolu Chen (Taylor & Francis Group, 2023)
AbstractContext Gouty arthritis (GA) is a characteristically inflammatory disease often associated with lipid metabolism disorder. Huangqin Qingrechubi capsule (HQC) has been used for the treatment of GA.Objective To explore the mechanism of HQC in the treatment of GA.Materials and methods A total of 30 GA patients (GA group) and 30 healthy subjects [normal control (NC) group] were recruited. The GA group was treated with HQC (3.6 g/d) for 10 days. Lipid metabolism and inflammation indexes were detected. Five herbal names of HQC, or 'gouty arthritis', 'hyperlipidemia' and 'inflammation' were used as key words to search related databases for network pharmacological analysis. Subsequently, GA-fibroblast-like synoviocytes (FLSs) were stimulated with GA-peripheral blood mononuclear cells (PBMCs) (3:1) and treated with HQC drug-containing serum (20%). RT-qPCR, Western blot, and ELISA were conducted to further explore the mechanism of HQC in improving GA.Results In clinical observation, HQC decreased the expression of lncRNA H19 and IL-1β, and increased the expression of adiponectin (APN) and IL-4 in the GA group (about half). Through network pharmacology, the PI3K/AKT signaling pathway was identified. Cell experiments showed that HQC treatment reduced the viability of GA-FLSs (49.61%), up-regulated the expression of IL-4 (155.18%), IL-10 (165.13%), and APN (31.24%), and down-regulated the expression of lncRNA H19 (33.70%), IL-1β (64.70%), TNF-α (78.32%), p-PI3K (48.80%), and p-AKT (53.48%).Discussion and conclusions HQC improved lipid metabolism disorder and inflammatory response of GA by regulating the lncRNA H19/APN/PI3K/AKT. Maintaining the stability of lipid metabolism may be an effective way to alleviate GA.